Maintenance of head and neck tumor on-chip: gateway to personalized treatment?. (7th March 2017) - Bower, Ruth; Green, Victoria L; Kuvshinova, Elena; Kuvshinov, Dmitriy; Karsai, Laszlo; Crank, Stephen T; Stafford, Nicholas D; Greenman, John
Aim: Head and neck squamous cell carcinomas (HNSCC) are solid tumors with low overall survival (40–60%). In a move toward personalized medicine, maintenance of tumor biopsies in microfluidic tissue culture devices is being developed.Methodology/results: HNSCC (n = 15) was dissected (5–10 mg) and either analyzed immediately or cultured in a microfluidic device (37°C) for 48 h. No difference was observed in morphology between pre- and postculture specimens. Dissociated samples were analyzed using trypan blue exclusion (viability), propidium iodide flow cytometry (death) and MTS assay (proliferation) with no significant difference observed highlighting tissue maintenance. Computational fluid dynamics showed laminar flow within the system.Conclusion: The microfluidic culture system successfully maintained HNSCC for 48 h, the culture system will allow testing of different treatment modalities with response monitoring. Lay abstract: Head and neck cancers often have a poor treatment outcome. In order to study the response of the tissue, a miniaturized culture system has been developed to keep a small piece of tumor alive. In the current study, we show that small pieces of cancer tissue can be maintained in the system, using tissue structure and viability of single cells as a guide. In future work, patient equivalent treatments can be applied to these microculture systems to investigate individual patient tumor responses, which could help to guide treatment selection.